Solidarity Action in Global Labor Networks. Four Cases of Workplace Organizing at Foreign Affiliates in the Global South - Wad, Peter (Nordic Journal of Working Life Studies, 2014)
Globalization transforms workforces of transnational corporation from predominantly home countrydominated workforces into foreign-dominated, multinational workforces. Thus, the national grounding of trade unions as the key form of labor organizing is challenged by new multinational compositions and cross-border relocations of corporate employment affecting working conditions of employees and trade unions in local places. We assume that economic globalization is characterized by expanding global corporate network of vertically and horizontally integrated (equity-based) and disintegrated (nonequity-based) value chains. We also assume that globalization can both impede and enable labor empowerment. Based on these premises the key question is, how can labor leverage effective power against management in global corporate networks? This question is split into two subquestions: a) How can labor theoretically reorganize from national unions and industrial relations institutions into global labor networks that allow prolabor improvement in global workplaces? b) How and why has labor in a globalized economy secured the core International Labor Organization (ILO) international labor right to organize companies and conduct collective bargaining? The Global Labor Network perspective is adopted as an analytical framework. Empirically, a comparative case methodology is applied comprising four more or less successful industrial disputes where labor achieved the right to organize and undertake collective bargaining. The disputes took place in affiliated factories of foreign transnational corporations located in Malaysia, the Philippines, Sri Lanka, and Turkey. The conclusion is that the combination of global labor capabilities and global labor strategizing must generate strategic labor power that adequately matches the weaknesses of the counterpart’s global corporate network in order to achieve prolabor outcomes. The most efficient solidarity action was leveraged by a cross-border alliance of workplace collectives, national industrial unions, and a global union federation using global framework agreements (GFAs) with key customers of the employer. The least efficient campaign relied primarily on domestic developing country state institutions supported by a foreign labor nongovernmental organization (NGO).